1988
DOI: 10.1111/j.1365-2125.1988.tb05278.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of bisoprolol and acebutolol in smokers with airway obstruction.

Abstract: 1. The effects of single oral doses of 10 mg bisoprolol and 400 mg acebutolol on respiratory function were studied in nine smokers with airway obstruction in a double‐blind, placebo‐controlled experiment. 2. The effects of the drugs were assessed by measuring specific airway conductance (sGaw) for 3 h after their administration and by studying their interaction with the bronchodilator response to inhaled salbutamol. 3. sGaw did not change for 3 h after bisoprolol or acebutolol administration. The bronchodilato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…This high safety margin has also been emphasized by Macquin-Mavier et al (1988), who showed that, contrary to acebutolol 400 mg, bisoprolol in doses of 10 mg has no effect on the dose-response curves of salbutamol in smokers with chronic bronchitis in agreement with Lammers et al (1984), Dorow & Tonnesmann (1984) and Dorow et al (1986).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This high safety margin has also been emphasized by Macquin-Mavier et al (1988), who showed that, contrary to acebutolol 400 mg, bisoprolol in doses of 10 mg has no effect on the dose-response curves of salbutamol in smokers with chronic bronchitis in agreement with Lammers et al (1984), Dorow & Tonnesmann (1984) and Dorow et al (1986).…”
Section: Discussionsupporting
confidence: 64%
“…The persistent partial 3-adrenoceptor blocking effects of acebutolol, elicited by a decrease in bronchial response to salbutamol or terbutaline, has also been demonstrated in asthmatics or in smokers with chronic bronchitis who received 400 mg of acebutolol (Greefhorst & van Herwaarden, 1982;Macquin-Mavier et al, 1988). In addition, Whitsett et al (1982) References are: (1) Duchin etal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical subject heading (MeSH) terms "respiratory tract diseases" and "adrenergic beta-antagonists" yielded 227 studies, 18 of which addressed the review objectives (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Key word searches "chronic obstructive lung disease" and "beta adrenergic receptor blocking agent" or "[beta-blocker name]" identified 2 further studies (23,24).…”
Section: Methodsmentioning
confidence: 99%
“…A Cochrane library meta-analysis concluded that long-term cardioselective beta-blockade is safe and well-tolerated in COPD (25,62). This meta-analysis evaluated pulmonary function in 20 randomized, controlled, crossover trials of cardioselective beta 1 -blockers in patients with COPD (Table 2) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). No study included any patients with HF.…”
Section: Randomized Trials Of Cardioselective Beta-blockade In Copdmentioning
confidence: 97%